Perbandingan Hasil Pemeriksaan Protein Urine Metode Carik Celup, Asam Asetat 6%, dan Asam Sulfosalisilat 20% Menggunakan Aturan Westgard - Permata Sari, Cecilia Febiyono; Kahar, Fitriani; Irnawati, Irnawati; Yusuf, Muhammad; Salam, Abdul; Wadood, Abdul (Jaringan Laboratorium Medis, 2023)
Proteinuria is caused by kidney damage. Qualitative examination of urine protein can be carried out using the dip strip method, 6% acetic acid and 20% sulfosalicylic acid. The aim of this research is to determine the accuracy and precision of urine protein examination using the dip strip method, 6% acetic acid and 20% sulfosalicylic acid. The research was experimental with repeated measurements of levels carried out visually and gave positive results of 1, 2, 3 and 4. The research was carried out in January 2022 using a research sample of 20 proteinuria positive patients at RSJD Dr. Amino Gondohutomo. The results of this research are that all methods meet the 12S rules where there is 1 control that is more than Â± 2SD (still in the Â± 3SD area), categorized as a warning/warning of method malfunction (needs more careful analysis). The best method is dip strip because it has the lowest Coefficient of Variation (KV) value, namely 0.497%. The method can still be used for patient care. The coefficient of variation obtained was dye liquid 0.497%, 6% acetic acid 0.654%, and 20% sulfosalicylic acid 0.630%. The smaller the KV value (%) the more thorough the system/method. The conclusion that can be drawn from this research is that the dip strip is a method that has the best accuracy and precision compared to the 6% acetic acid and 20% sulfosalicylic acid methods because it has the smallest coefficient of variation (KV%) value, namely 0.497% and meets the 12S rules. Researchers recommend always ensuring that the research location has the required samples with adequate volume, urine protein examination can be carried out using the dip strip method, researchers can then carry out urine protein examination regarding the sensitivity and specificity of the three qualitative methods